Study on the Behavioural Assessment of the Dysexecutive Syndrome (BADS) performance in healthy individuals, Mild Cognitive Impairment and Alzheimer's disease: A preliminary study - Armentano,Cristiane Garcia da Costa (2009)
Abstract Executive deficits as well as deficits in episodic memory characterize the initial phases of Alzheimer Disease (AD) and are clinically correlated to neuropsychiatric symptoms and functional loss. Patients with Mild Cognitive Impairment present more problems as to inhibitory response control, switching and cognitive flexibility. Objective: To compare performance on the BADS with performance on other executive functional tests among patients with mild Alzheimer's disease, Amnestic Mild Cognitive Impairment (aMCI) to performance of control individuals and to examine discriminative capacity of BADS among these groups. Methods: The BADS was performed by 35 healthy controls, 13 patients with aMCI, and 16 mild probable AD patients. Besides performing the BADS, subjects underwent neuropsychological evaluation which comprised: the Dementia Rating Scale (DRS), verbal fluency by phonemic categories (F.A.S) and Concentrated Attention Test (CA). Results: There were no differences among groups by educational level, but performance differed for age (p<0.01). No difference between healthy controls and aMCI patients was found on total scores or subitems of the BADS. A significant difference was observed between aMCI and AD patients (p<0.05) and between controls and AD patients (p<0.05) on total and standard scores. Conclusions: Performance on the BADS differed between healthy individuals and mild AD patients. The BADS proved to be a sensitive method for discriminating AD from aMCI.